A pragmatic approach to monitor and evaluate implementation and impact of differentiated ART delivery for global and national stakeholders. Issue 3 (14th March 2018) - Ehrenkranz, Peter D; Calleja, Jesus MG; El‐Sadr, Wafaa; Fakoya, Ade O; Ford, Nathan; Grimsrud, Anna; Harris, Kate L; Jed, Suzanne L; Low‐Beer, Daniel; Patel, Sadhna V; Rabkin, Miriam; Reidy, William John; et al.
Abstract: Introduction: The World Health Organization's (WHO) recommendation of "Treat All" has accelerated the call for differentiated antiretroviral therapy (ART) delivery, a method of care that efficiently uses limited resources to increase access to HIV treatment. WHO has further recommended that stable individuals on ART receive refills every 3 to 6 months and attend clinical visits every 3 to 6 months. However, there is not yet consensus on how to ensure that the quality of services is maintained as countries strive to meet these standards. This commentary responds to this gap by defining a pragmatic approach to the monitoring and evaluation (M&E) of the scale up of differentiated ART delivery for global and national stakeholders. Discussion: Programme managers need to demonstrate that the scale up of differentiated ART delivery is achieving the desired effectiveness and efficiency outcomes to justify continued support by national and global stakeholders. To achieve this goal, the two existing global WHO HIV treatment indicators of ART retention and viral suppression should be augmented with two broad aggregate measures. The addition of indicators measuring the frequency of (1) clinical and (2) refill visits by PLHIV per year will allow evaluation of the pace of scale up while monitoring its overall effect on the quality and efficiency of services. The combination of these four routinely collected aggregate indicators will also facilitate the comparison of outcomes among facilities, regions or countries implementing different models of ART delivery. Enhanced monitoring or additional assessments will be required to answer other critical questions on the process of implementation, acceptability, effectiveness and efficiency. Conclusions: These proposed outcomes are useful markers for the effectiveness and efficiency of the health system's attempts to deliver quality treatment to those who need it—and still reserve as much of the available resource pool as possible for other key elements of the HIV response.